PEREMPUAN, SPIRITUALITAS, DAN PERUBAHAN SOSIAL: ANALISIS TERHADAP PERAN SARATHI DALAM MASYARAKAT HINDU KONTEMPORER - Raharjo, Sukirno Hadi; Ningrum, Siti Utami Dewi (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2024)
This research aims to analyse the role of women as Sarathi in Hindu religious rituals and their impact on social change in contemporary Hindu society. The focus of this research is to explore the gender dynamics contained in the involvement of women as Sarathi, as well as how this role influences spirituality and its contribution to social change. Through a qualitative approach, this research will conduct an in-depth analysis of the experiences and perceptions of women who carry out the role of Sarathi in the Hindu religious context. The research will also highlight the challenges and opportunities women face in carrying out these ritualistic roles and their impact on structural changes in contemporary Hindu society. It is hoped that the results of this research will provide a better understanding of the contribution of women in the Hindu religious context, explore the potential of women as agents of social change, and strengthen dialogue regarding gender equality in the religious realm. In addition, it is hoped that this research can provide a basis for policies and advocacy that support women's empowerment and encourage gender equality in the continuing developing Hindu religious context.